2010
DOI: 10.1038/pj.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline-doped benzene sulfonic acid/epoxy resin composites: structural, morphological, thermal and dielectric behaviors

Abstract: Conducting polymer composites, which are simply physical mixtures of an insulating polymer matrix and intrinsically conducting polymers, are promising new materials for various applications such as antistatic coatings, shielding and electromagnetic absorbers. In this context, a novel conducting composite was successfully produced. It is based on epoxy resin and polyaniline (PANI) doped in benzene sulfonic acid, which was used as conducting filler. The effect of PANI loading levels on the structural, morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 49 publications
(29 reference statements)
1
42
0
Order By: Relevance
“…3) that is assigned to vibration of a delocalized polaron structure (Belaabed et al 2010). The band at 1502 cm −1 (arrow in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…3) that is assigned to vibration of a delocalized polaron structure (Belaabed et al 2010). The band at 1502 cm −1 (arrow in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Chauhan et al (2011), studying the thermal behavior of emeraldine base PANI, reported two significant different events: one in the range of 25°C to 60°C, credited to the evaporation of adsorbed water, and a second between 90°C to 115°C due possibly to cross-linking reactions between nearby quinoidal rings in the structure of the polymer. Belaabed et al (2010) found that the PANI-doped BSA is thermally stable up to 600 ºC working in a nitrogen flow (20 mL/min) and a heating rate of 5 ºC/min, reporting that only 40% of weight loss was observed. Three significant events of weight loss were verified: the first in the range of 30 to 170 ºC, caused by the loss of absorbed water and oligomers.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…These observations are in agreement with the thermogram obtained by thermogravimetric analysis (Figure 2). 16 The evaporation and degradation of BSA and the oxidation process of the PANI structure and its composites occurred between 170 and 390 1C. 7,18,19 To avoid deprotonation of the conducting PANI and maintain the conductivity of composites after the curing process, it was imperative to add a catalyst.…”
Section: Dsc Studymentioning
confidence: 99%
“…PANI-doped BSA with an [oxidant]/[aniline] molar ratio of B1.15 was prepared at À17 1C. 16 The product exhibited an electrical conductivity of 8-10 S m À1 as a pressed pellet. To ensure adequate dispersion, the PANI was dispersed in tetrahydrofuran for 3 h at room temperature using an ultrasonic bath, followed by magnetic stirring to improve the dispersion's quality.…”
Section: Composite Preparationmentioning
confidence: 99%
See 1 more Smart Citation